2020
DOI: 10.1007/s11684-020-0810-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study using mesenchymal stem cells for the treatment of patients with severe COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 was identified in December 2019. The symptoms include fever, cough, dyspnea, early symptom of sputum, and acute respiratory distress syndrome (ARDS). Mesenchymal stem cell (MSC) therapy is the immediate treatment used for patients with severe cases of COVID-19. Herein, we describe two confirmed cases of COVID-19 in Wuhan to explore the role of MSC in the treatment of COVID-19. MSC transplantation increases the immune indicators (including CD4 and lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 52 publications
3
113
0
1
Order By: Relevance
“…MSC-based therapy protocols to treat COVID-19 have been directed mainly to patients with moderate and severe clinical presentations [9][10][11][12][13][14][15][16][17][18]. Few numbers of studies included critically ill patients with COVID-19 under invasive mechanical ventilation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC-based therapy protocols to treat COVID-19 have been directed mainly to patients with moderate and severe clinical presentations [9][10][11][12][13][14][15][16][17][18]. Few numbers of studies included critically ill patients with COVID-19 under invasive mechanical ventilation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSCs) have been evaluated in compassionate use or clinical trials to treat COVID-19 pneumonia [9][10][11][12][13][14][15][16][17][18]. The rationale is to direct the immunomodulatory properties of MSCs to control the hyperin ammatory state and improve respiratory function.…”
mentioning
confidence: 99%
“…During 2014-2020, several clinical studies published their results on MSC therapy for ARDS patients with safety results and/or without serious adverse events (Table 1) [10,[16][17][18][19]. Furthermore, several case reports have been published on MSC therapy in severe COVID-19 patients and demonstrated that MSC transplantation resulted in valuable clinical data on the treatment of COVID-19 and it may be an alternative approach for treating COVID-19, notably in patients with ARDS [12,13]. The MSCs could perform in two significant ways for the COVID-19 treatment, including in immunomodulatory effects and differentiation potency.…”
Section: Cell-based Clinical Trials For Covid-19mentioning
confidence: 99%
“…Indeed, regardless of the organ, SARS-CoV-2 infection causes disseminated inflammatory reactions, so therapies that bear immunomodulatory effects are welcome to treat COVID-19. Corroborating this idea, several clinical trials using MSC or their derived products are now ongoing and eight clinical studies were already concluded and reported interesting results, as most COVID-19 patients recovered a few days after treatment [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. However, only one of these studies incorporated appropriate control groups and a considerable number of patients.…”
Section: Introductionmentioning
confidence: 99%